2020
DOI: 10.1111/sjop.12652
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to behavior problems in Norwegian kindergarten children: The role of parent emotion socialization and child emotion understanding

Abstract: Pathways to behavior problems in Norwegian kindergarten children: The role of parent emotion socialization and child emotion understanding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 69 publications
4
17
0
2
Order By: Relevance
“…Nonsupportive parental behaviors predicted increasing externalizing problems, while supportive behaviors predicted a decrease in child externalizing. This is supported by a Norwegian study of the relation between parent emotion socialization and child emotion understanding and externalizing behavior, using baseline measures from the same sample as in the current study (Bjørk et al, 2020). They showed that higher levels of parental distress in response to children's negative emotion (i.e., non-supportive parenting) was associated with higher levels of externalizing child behavior and supportive parental responses were significantly correlated with child emotion understanding.…”
Section: Emotion Socialization Interventions and Child Anxiety And Externalizing Problemssupporting
confidence: 81%
“…Nonsupportive parental behaviors predicted increasing externalizing problems, while supportive behaviors predicted a decrease in child externalizing. This is supported by a Norwegian study of the relation between parent emotion socialization and child emotion understanding and externalizing behavior, using baseline measures from the same sample as in the current study (Bjørk et al, 2020). They showed that higher levels of parental distress in response to children's negative emotion (i.e., non-supportive parenting) was associated with higher levels of externalizing child behavior and supportive parental responses were significantly correlated with child emotion understanding.…”
Section: Emotion Socialization Interventions and Child Anxiety And Externalizing Problemssupporting
confidence: 81%
“…Emotion coaching describes supportive responses to children's emotions, whereby parents believe emotions are desirable, have high emotion awareness and regulation, and validate, encourage, and accept children's emotion expression (Denham et al, 2007;Havighurst et al, 2013;Katz et al, 2012). Emotion coaching is associated with optimal child development, such as improved emotion competence (Bjørk et al, 2020;Buckholdt et al, 2016;Gottman et al, 1996).…”
Section: Meta-emotion Theorymentioning
confidence: 99%
“…Although the majority of items describe parents' comfort/soothing behaviors, most items also refer to parents distracting children from negative emotions (e.g., "…comfort my child and try to get him/her to think about something happy"). Gottman et al (1996), and other emotion socialization researchers (Bjørk et al, 2020;Denham & Burton, 2003;Eisenberg, 1996;Halberstadt et al, 2008;Magai & O'Neal, 1997), consider emotion distraction an emotion dismissing response that does not facilitate emotion competence, because emotion distraction does not provide children the opportunity to discuss and understand their emotions (Shenk & Fruzzetti, 2014).…”
Section: Short-form Ccnesmentioning
confidence: 99%
See 2 more Smart Citations